Untapped the scramble for Africa's oil - Ghazvinian, John. (Orlando Harcourt, 2007)
Africa- a region long known to be rich in oil-is the scene of a competition between major powers that recalls the nineteenth-century scramble for colonization there. But what does this new oil boom mean- for America, for the world, for Africans themselves? To find out, John Ghazvinian traveled through twelve African countries-from Sudan to Congo to Angola-talking to warlords, industry executives, bandits, activists, priests, missionaries, oil-rig workers, scientists, and ordinary people whose lives have been transformed by the riches beneath their feet. The result is a high-octane narrative that reveals the reasons for despair and reasons for hope emerging from the world's newest energy hot spot.
Includes bibliographical references and index.
Keywords: Petroleum industry and trade - Africa